Crude extract and isolated bioactive compounds from Notholirion thomsonianum (Royale) Stapf as multitargets antidiabetic agents: in-vitro and molecular docking approaches - Mater H. Mahnashi; Yahya S. Alqahtani; Ali O. Alqarni; Bandar A. Alyami; Muhammad Saeed Jan; Muhammad Ayaz; Farhat Ullah; Umer Rashid; Abdul Sadiq (BMC, 2021)
Abstract Background Diabetes mellitus is a common disease effecting the lifestyles of majority world population. In this research work, we have embarked the potential role of crude extracts and isolated compounds of Notholirion thomsonianum for the management diabetes mellitus. Methods The crude extracts of N. thomsonianum were initially evaluated for α-glucosidase, α-amylase and antioxidant activities. The compounds were isolated from the activity based potent solvent fraction. The structures of isolated compounds were confirmed with NMR and MS analyses. The isolated compounds were tested for α-glucosidase, α-amylase, protein tyrosine phosphatase 1B (PTP1B) and DPPH activities. The molecular docking studies were carried out to find the binding interactions of isolated compounds for α-glucosidase, α-amylase and PTP1B. Results Initially, we screened out crude extracts and subfractions of N. thomsonianum against different in-vitro targets. Among all, Nt.EtAc was observed a potent fraction among all giving IC50 values of 67, 70, < 0.1, 89 and 16 μg/mL against α-glucosidase, α-amylase, DPPH, ABTS and H2O2 respectively. Three compounds (Nt01, Nt02 and Nt03) were isolated from Nt.EtAc of N. thomsonianum. The isolated compounds Nt01, Nt02 and Nt03 exhibited IC50 values of 58.93, 114.93 and 19.54 μM against α-glucosidase, while 56.25, 96.54 and 24.39 μM against α-amylase respectively. Comparatively, the standard acarbose observed IC50 values were 10.60 and 12.71 μM against α-glucosidase, α-amylase respectively. In PTP1B assay, the compounds Nt01, Nt02 and Nt03 demonstrated IC50 values of 12.96, 36.22 and 3.57 μM in comparison to the standard ursolic acid (IC50 of 3.63 μM). The isolated compounds also gave overwhelming results in DPPH assay. Molecular docking based binding interactions for α-glucosidase, α-amylase and PTP1B were also encouraging. Conclusions In the light of current results, it is obvious that N. thomsonianum is potential medicinal plant for the treatment of hyperglycemia. Overall, Nt.EtAc was dominant fraction in all in-vitro activities. Three compounds Nt01, Nt02 and Nt03 were isolated from ethyl acetate fraction. The Nt03 specifically was most potent in all in-vitro assays. The molecular docking studies supported our in-vitro results. It is concluded that N. thomsonianum is a rich source of bioactive antidiabetic compounds which can be further extended to in-vivo based experiments.